(untitled) (Revista Internacional de Folkcomunicação, 2025)
This article investigates how audiovisual narratives about popular legends contribute to collective memory and the memory of the place, bringing together the concepts of folk media and documentary. Based on the Lendas de Navegantes project, which produced mini-documentaries based on oral accounts, the objective is to understand how audiovisual narrative strategies update traditional knowledge, making it attractive to new generations. The research starts from the question: how do audiovisual narratives of documentaries about popular legends contribute to collective memory? The methodology includes the description of the project’s production process and the application of Critical Narrative Analysis (Motta, 2013) to the mini-documentaries, examining aesthetic, symbolic and narrative resources. The results indicate that documentaries can operate on two levels: using narrative strategies that have a real-life effect, with testimonies from residents, soundscapes and current images, conferring verisimilitude and reinforcing community belonging; and in the poetic effect, with animations, soundtracks and symbolic resources that update and resignify the legends. The research concludes that these productions function as cultural mediators, preserving orality, strengthening identity bonds and contributing to heritage education. In addition to entertainment, mini-documentaries become pedagogical and political instruments, capable of promoting dialogue between tradition and contemporaneity, inserting popular manifestations into the digital media environment.